2020
DOI: 10.1016/j.psyneuen.2020.104719
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal and modality specific effects on males’ emotion recognition ability

Abstract: Successful emotion recognition is a key component of our socio-emotional communication skills. However, little is known about the factors impacting males' accuracy in emotion recognition tasks. This pre-registered study examined potential candidates, focusing on the modality of stimulus presentation, emotion category, and individual hormone levels. We obtained accuracy and reaction time scores from 312 males who categorized voice, face and voice-face stimuli for nonverbal emotional content. Results showed that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 136 publications
0
13
0
Order By: Relevance
“…The lack of a significant mediation effect by FTI may be explained by unmeasured factors associated with both AAS use and ERT. Previous studies testing the association between testosterone and social cognition have reported both positive and negative associations (Lausen et al 2020 ; Nadler et al 2019 ; Vongas and Al Hajj 2017 ). This heterogeneity in results is potentially a result of complex interactions between environmental and biological variables.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The lack of a significant mediation effect by FTI may be explained by unmeasured factors associated with both AAS use and ERT. Previous studies testing the association between testosterone and social cognition have reported both positive and negative associations (Lausen et al 2020 ; Nadler et al 2019 ; Vongas and Al Hajj 2017 ). This heterogeneity in results is potentially a result of complex interactions between environmental and biological variables.…”
Section: Discussionmentioning
confidence: 98%
“…This heterogeneity in results is potentially a result of complex interactions between environmental and biological variables. For example, relationships between testosterone and social cognition and behaviors can be moderated by cortisol or competition (Carré et al 2014 ; Lausen et al 2020 ; Wagels et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for lack of replication across development may be related to how sex balance across proband groups distributes the relationship between puberty, hormones, and social cognition. Females are better at emotion recognition tasks than males [ 35 , 36 ] and there is evidence that late-pubescent and post-pubescent individuals are generally better able to recognize emotions than those in early puberty or prepubescents ( e . g ., the PNC young proband group) [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the potential limitations in the current study could stem from combining two datasets collected within the scope of two large studies (see Lausen et al, 2020;Rafiee et al, 2023).…”
Section: Limitations and Outlookmentioning
confidence: 99%